Hidden in the heart: A peculiar type of left ventricular remodeling after acute myocardial infarction. Issue 11 (25th August 2017) - Cicenia, Marianna; Fedele, Francesco; Petronilli, Valentina; De Carlo, Carlotta; Moscucci, Federica; Schina, Mauro; Sciomer, Susanna
Abstract : We reported an unusual case of left ventricular pouch, in a 72‐year‐old man who had an acute coronary syndrome treated with percutaneous revascularization. The echocardiogram showed a sort of pouch, delimited by epicardium and endocardium, confirmed by 3D echo. This finding appeared as an echo free area, with a really slight color flow inside. We consequently supposed it would be a dissecting hematoma, a rare complication of the ischemic disease, due to the rupture of the intramyocardial vessels among the spiral myocardial fibers. This would produce a hemorrhagic pouch contained by epicardial and endocardial layers, which could evolve into mural thrombi.